2005
DOI: 10.1891/jnum.2005.13.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire Development to Predict Mammography Intention Among Women in Southeastern Louisiana

Abstract: This article summarizes the development and psychometric analysis of the Thoughts About Mammography (TAM) questionnaire to predict mammography intention using the Theory of Planned Behavior (TPB). Key themes, obtained from elicitation interviews (N = 45), were categorized, ranked and extracted for item construction. Initial pilot testing supported test-retest reliability (alpha = .85 to .97), internal consistency (alpha = .67 to .91), and content validity (0.86-1.00). After pilot testing, the TAM was administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…In a study by Halm et al (2007) on gastric cancer, behavioral attitudes showed a significant influence, whereas subjective norms did not. Similarly, in studies by Steele et al (2005) on breast cancer and Berglund et al (2005) on prostate cancer, behavioral attitudes showed a significant influence. Conversely, Tolma et al (2006) showed that behavioral attitudes were not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…In a study by Halm et al (2007) on gastric cancer, behavioral attitudes showed a significant influence, whereas subjective norms did not. Similarly, in studies by Steele et al (2005) on breast cancer and Berglund et al (2005) on prostate cancer, behavioral attitudes showed a significant influence. Conversely, Tolma et al (2006) showed that behavioral attitudes were not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…Montano et al (11) confirmed a significant correlation between previous experience with breast cancer screening and intention. Steele and Porche et al (14) reported that people who had experience with a prostate-specific antigen (PSA) test to screen for prostate cancer were likely to have a high intention of requesting a PSA test in the future. An awareness of the screening cost negatively influenced the intention when screening was not available free of charge or for a copayment.…”
Section: Discussionmentioning
confidence: 99%
“…Causality cannot be determined with cross-sectional survey data and future prospective studies will need to confirm the associations reported here. Most studies using the theory of planned behavior model to assess screening behavior have simultaneously surveyed cognitive factors and intention, and then checked behavior (8,9,12,14). We need to do a further study to confirm that the intention to receive stomach cancer screening influences the behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations